Language Learning Strategies in the Writing Process: A Qualitative Inquiry of Senior High School Students' Experiences - Ranti Setia Putri; Marzul Hidayat; Noprival Noprival; Hadiyanto Hadiyanto; Mukhlash Abrar (FKIP - Universitas Riau, 2026)
Writing in English as a Foreign Language (EFL) presents persistent cognitive and metacognitive challenges for Indonesian senior high school students. Despite growing evidence that Language Learning Strategies (LLS) mediate writing performance, the specific strategies students employ across different stages of the composing process remain underexplored at the secondary level in Indonesia. This qualitative case study investigates the LLS employed by six purposively selected Grade XI students (two per achievement level: high, mid, and low) in Jambi City during the English writing process and examines their perceptions of the role those strategies play in supporting writing development. Data were collected through semi-structured interviews analyzed using thematic analysis following Braun and Clarke's (2021) six-phase framework and Oxford's (1990, 2017) LLS taxonomy. Results reveal differentiated strategic profiles across participants: higher-achieving students deployed broad, metacognitively orchestrated repertoires across all writing stages, while lower-achieving students relied predominantly on compensatory and translation-based strategies with limited metacognitive engagement. The study underscores the critical role of metacognitive strategy use in EFL writing and calls for explicit, contextualized strategy instruction integrated into the process writing curriculum at the Indonesian secondary level.